Evaluating Misconceptions in the Representation of Mendelian Genetic Inheritance in High School Biology Textbooks - Kusniawati Kusniawati; Wolly Candramila; Eko Sri Wahyuni (Tropical Genetics, 2025)
Genetics learning is prone to misconceptions due to complex concepts, abstract reasoning, and inconsistencies in textbook presentations, which can hinder students’ understanding of inheritance patterns such as Mendelian genetics. This study analyzes the potential misconceptions in high school biology textbooks regarding Mendel’s Laws and dominance–recessive inheritance using Dikmenli et al.’s categorization, aiming to provide references for teachers in selecting and supplementing instructional materials. This is a descriptive qualitative research using content analysis method. Four textbooks, selected through a survey of biology teachers in Pontianak City, were analyzed by comparing key concepts in the textbooks with scientifically accurate explanations from authoritative references. The findings were systematically examined, categorized, and validated through member-checking to ensure accuracy, highlighting the most common types of misconceptions in the textbooks. The analysis revealed variations in the coverage and accuracy of 13 key concepts related to Mendel’s Laws and dominance–recessive inheritance, with Books A–C containing several potential misconceptions while Book D showed none. The most frequent types of misconceptions identified were misidentifications, followed by oversimplifications and overgeneralizations, often involving definitions of gene, genotype, phenotype, and independent assortment. These findings highlight the importance of accurate textbook content and suggest that educators must critically evaluate and clarify textbook explanations to prevent persistent misunderstandings in students’ conceptual understanding of genetics.